PERANAN TOKOH MASYARAKAT DALAM PENGENDALIAN PERILAKU BERISIKO HIV/AIDS - Handayani, Sri; Angelia, Inge; Fitri, Wiya Elsa (Poltekkes Kemenkes Bandung, 2023)
The incidence of HIV/AIDS is still high and continues to increase. The Indonesian Ministry of Health's report on P2P in 2019 in Indonesia was 50,282 HIV cases and 7,036 AIDS cases. West Sumatra is ranked 19th regarding the highest number of HIV cases with 541 HIV cases and 258 AIDS cases. The HIV incidence rate in Padang City in 2019 was 287 cases. The aim of this research is to determine the role of bundo kanduang and religious scholars in controlling HIV/AIDS. This research uses quantitative cross-sectional methods. The research will be conducted in Padang City, Payakumbuh City, Fifty Cities Regency, Bukitinggi City and Pasaman Regency in West Sumatra Province with a sample size of 104 people. The research was conducted from August 2021 to December 2022. The research procedures that will be carried out are data collection, data analysis and data interpretation. Data was collected using a questionnaire with data sources namely primary and secondary data. Data were analyzed computerized using SPSS version 25, univariate and bivariate. The results of the research obtained information that there was a relationship between the role of biological mother (p-value = 0.001) and religious ulama (p-value = 0.000) with HIV/AIDS risk behavior. Based on statistical results, information was obtained that there is a relationship between biological parents and religious scholars with HIV/AIDS risk behavior. It is hoped that the West Sumatra government will again increase the role of community leaders by involving community leaders in preparing plans to control HIV/AIDS in the community.